COMPARATIVE ANALYSIS OF THE CONTENT OF THE TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV’S LINGUISTIC EDUCATIONAL MUSEUM EXPOSITION WITH SIMILAR INSTITUTIONS IN THE WORLD - Бочарнікова, А. (Київський національний університет імені Тараса Шевченка, Навчально-науковий інститут філології, 2019)
The article contains information on all general-purpose linguistic museums that are currently functioning in the world, functioned in the past, or are at the project stage. In cases where this is possible, the structure of museum’s exposition is examined. Criteria that have played a key role in the division of museums’ content into structural elements are defined. The accuracy of exposition authors’ compliance of their approaches has also been analyzed. The first linguistic museum in the world that opened its doors to visitors was Taras Shevchenko university of Kyiv’s Linguistic Educational Museum founded in 1992 by the order of the university’s rector. During next sixteen years it was world’s only linguistic museum till the year 2008 when National Museum of Language in the US was opened. In 2013 a new linguistic museum named Mundolingua was established in Paris. After 2014 when the museum in USA was closed and till now it continues to be the only linguistic museum in the world except Linguistic Educational Museum in Ukraine that is functioning. At present times there are several big projects of establishing a comprehensive linguistic museum in diﬀerent countries. Among them is Planet Word  in Washington, Museum der Sprachen der Welt   in Berlin, Museum of Language in London. The work upon these projects is in progress and hasn’t reached the stage of completeness. There are also two websites available on the Internet that have the name of museum but does not contain any traces of the exposition content. These are the website of the above mentioned National Museum of Language and Taalmuseum in the Netherlands. Both of these websites are portals for announcements concerning exhibitions, lectures and meetings in diﬀerent places that are somehow referred to language topics. In this article the structure of the museums content has also been analyzed. Linguistic Educational Museum in Kyiv was established for academic purposes therefore its content has the same structure as the Introductory Linguistics course. At the same time it reveals the principles of the museum exposition author’s Doctor of Science thesis named the Metatheory of Linguisics.

У статті зібрано інформацію про всі лінгвістичні музеї загального спрямування, які на сьогодні функціонують у світі, функціонували в минулому або знаходяться на стадії проекту. У випадках, де це є можливим, досліджено структуру експозиції музеїв. Визначено критерії, які відіграли ключову роль при розподілі експозиції на структурні елементи. Проаналізовано міру послідовності дотримання авторами експозиції музеїв застосованих ними підходів. ____________ ЛІТЕРАТУРА Тищенко, К.М. Метатеорія мовознавства. К. : Основи, 2000. 352 с. 2. Тищенко, К.М. Основи мовознавства. Системний підручник. К. : Київський університет, 2007. 304 с. 3. Lan- guage Museums of the World. Ed. by O. Grepstad Orsta : Centre for Norwegian Language and Lite- rature, 2018. 134 p. 4. URL : http://archasm.in/museum-of-language-top-50/ 5. URL : https://www. chronicle.com/blogs/linguafranca/2017/01/31/a-language-museum/ 6. URL : https://www.govtilr.org/ Publications/NML_Presentation.pdf 7. URL : https://www.insidephilanthropy.com/home/2019/3/5/ planet-word-a-philanthropists-mission-to-build-a-museum-of-language 8. URL : http://language- museum.org/about/history/ 9. URL : http://www.linguaemundi.info/sprachmuseum-was-ist-das/  10.        URL : http://mentalﬂoss.com/article/91608/linguistics-museum-coming-washington-dc 11. URL : http://www.mundolingua.org/en/ 12. URL : https://taalmuseumleiden.nl/ﬁles/2018-02/taal-prospectus. pdf?9a1f9af427
Порівняльний аналіз змістового наповнення експозиції лінгвістичного навчального музею КНУ імені Тараса Шевченка з аналогічними установами світу
Keywords: linguistic museum; exposition structure; introductory linguistics course; лінгвістичний музей; структура експозиції; основи мовознавства